2010
DOI: 10.1016/j.contraception.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive efficacy of emergency contraception with levonorgestrel given before or after ovulation

Abstract: We conclude that LNG-EC prevents pregnancy only when taken before fertilization of the ovum has occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…In summary, under the conditions studied, LNG caused minimal changes in transcripts levels and, considering their nature and magnitude, it is unlikely they would interfere with endometrial receptivity an assumption confirmed by the studies of Novikova et al (2007) and Noe et al (2010) cited above.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In summary, under the conditions studied, LNG caused minimal changes in transcripts levels and, considering their nature and magnitude, it is unlikely they would interfere with endometrial receptivity an assumption confirmed by the studies of Novikova et al (2007) and Noe et al (2010) cited above.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, low doses of mifepristone administered in the luteal phase alter endometrial maturation (Greene et al 1992) and other antiprogestins, such as onapristone produce the same pattern of endometrial alterations (Katkam et al 1995) that will inhibit endometrial receptivity providing a basis of their development for endometrial contraception (Cameron et al 1997) whereas no effects of post-ovulatory LNG administration on the histological features of the endometrium examined during the receptive phase were found (Durand et al 2001, Marions et al 2002. Furthermore, two independent studies have shown that emergency contraception with LNG given before ovulation prevents pregnancy in all treated women and that it fails completely to prevent pregnancy when it is given after ovulation (Novikova et al 2007, Noe et al 2010, confirming the use of LNG as an effective contraceptive method only if it is taken before ovulation. Those two studies provide functional evidence that the few changes in gene expression described here are irrelevant for endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…When taken as instructed, levonorgestrel tablets can reduce the risk of pregnancy by approximately 80% (per “plan B” label, for example) relative to the number of pregnancies that would be expected to occur with unprotected intercourse [16], [25], [26]. This product type is only effective when taken before ovulation [27], [28].…”
Section: Discussionmentioning
confidence: 99%
“…6 Therefore, because the risk of pregnancy is highest in the two days leading up to ovulation, ulipristal acetate is probably more effective than levonorgestrel. Levonorgestrel is not effective after fertilisation, 7 and it is unclear whether ulipristal acetate has any effect after ovulation.…”
Section: How Does It Work? Intrauterine Devicementioning
confidence: 99%